Familial genetic cancer risk assessment in a male patient with pancreatic and breast cancer with a silent BRCA2 mutation (Indian Journal of Case Reports, 2024)
Male breast cancer (MBC) is relatively rare, accounting for <1% of cancers in men. Hereditary MBC is mainly attributed to BRCA1/2 germline mutations. Accordingly, National Comprehensive Cancer Network guidelines advise genetic counseling and testing for all cases of MBCs and their unaffected family members. In this report, we present an uncommon case of a male patient in his late 50s primarily diagnosed with pancreatic cancer who later developed asynchronous bilateral hormone-positive breast cancer. Genetic testing revealed a “pathogenic/likely pathogenic” BRCA2 variant (c.8754G >A, pE2918E) in the proband. Cascade testing of 34 family members identified 5 of the family members as carriers of this BRCA2 variant. Among them, two members were breast cancer affected and three were unaffected healthy carriers. Our study demonstrates the clinical relevance of this silent BRCA2 mutation and emphasizes the need for further experimental studies to elucidate its functional role in breast cancer pathology.